2019
DOI: 10.1111/exd.14015
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐17A affects extracellular vesicles release and cargo in human keratinocytes

Abstract: Psoriasis is a chronic inflammatory systemic disease caused by deregulation of the interleukin‐23/‐17 axis that allows the activation of Th17 lymphocytes and the reprogramming of keratinocytes proliferative response, thereby inducing the secretion of cyto‐/chemokines and antimicrobial peptides. Beside cell‐to‐cell contacts and release of cytokines, hormones and second messengers, cells communicate each other through the release of extracellular vesicles containing DNA, RNA, microRNAs and proteins. It has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…In addition to EV-bound miRNAs, we screened the physical characteristics of the isolated EVs, such as their size, ZP and surface proteome, to find potential biomarkers in plaque psoriasis and psoriatic arthritis. The size distributions of serum EVs and their ZP profile can be viewed as proxy biomarkers with the presence of changes in the size distributions of EVs revealing the state of their origin cells [ 32 , 79 ]. The ZP value of EVs, which is related to their surface charge, is in turn affected by the protein composition of its lipid bilayer [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to EV-bound miRNAs, we screened the physical characteristics of the isolated EVs, such as their size, ZP and surface proteome, to find potential biomarkers in plaque psoriasis and psoriatic arthritis. The size distributions of serum EVs and their ZP profile can be viewed as proxy biomarkers with the presence of changes in the size distributions of EVs revealing the state of their origin cells [ 32 , 79 ]. The ZP value of EVs, which is related to their surface charge, is in turn affected by the protein composition of its lipid bilayer [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that keratinocyte exosomes are implicated in the activation of neutrophils and intensifying inflammation [ 31 ]. In addition, Mangino and colleagues have reported that L17A-treated keratinocytes secrete fewer EVs; however, PsV-related mRNAs (DEFB4, CXCL-family ligands) are abundant in these EVs, providing further evidence for EVs mediating pathological signals in PsV [ 32 ]. In a study by Marton et al, it was shown that the circulatory EVs from PsA patients are unable to suppress osteoclast differentiation in vitro, compared to those extracted from the blood of healthy individuals and rheumatoid arthritis patients [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to EVs derived from other cells, keratinocyte-EVs also vary in composition and abundance of contents depending on the parent cell status and stimulus. For example, IL-17A-treated keratinocytes released EVs containing β-defensin 2 and chemoattractants such as CXCL1, CXCL3, CXCL5, and CXCL6 125 . In addition, Staphylococcus aureus ( S. aureus ) enterotoxin B-loaded HaCaT cells (a keratinocyte cell line) released EVs containing MHC molecules, which promoted CD4 + and CD8 + T cell proliferation in vitro 126 .…”
Section: Characteristics and Functions Of Evs From Cells Associated Wmentioning
confidence: 99%
“…A number of studies have shown that endothelial cell- and platelet-derived EVs were increased in patients with psoriasis 157 - 161 , were positively correlated with the psoriasis area and severity index score 157 , and were decreased by anti-TNF-αbut not anti-IL-12/23 treatment 162 . Besides, psoriasis-related cytokines modulated the production of EVs, as IL-17A induced HaCaT cells to produce EVs carrying the mRNAs of several chemokines and β‐defensin 2 125 . Recent studies attempted to analyze the miRNA profiles in plasma-derived EVs to illustrate their potential as future psoriasis biomarkers 17 , 163 .…”
Section: Ev Involvement In the Pathophysiology Of Inflammatory Skin Dmentioning
confidence: 99%
“…Many studies have shown that Th17 cells and the Th17 pathway play a more and more important role in the occurrence and development of psoriasis. As a downstream effector molecule of Th17 cells, interleukin-17A (IL-17A) can induce fibroblasts and epithelial cells to secrete a variety of cytokines and promote local inflammation [ 6 ]. Lin et al demonstrated that the increased number of mast cells and neutrophils in psoriatic lesions contributes to the release of the pathogenic cytokine IL-17A through EV formation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%